Challenges and Strengths of Supermarket - Rathod, Raju M. (Indian Journal of Marketing, 2004)
As progress moved across America in the late 1800’s and early 1900’s, millions of bright men and women opened Main Street stores. The first half of the twentieth century saw the arrival and the growth of large retail giants. This new group of discount stores redefined value and varieties with low prices and wide inventories. Though, the arrival of supermarkets in India was a bit late but they are fast becoming the rage amongst the retail enthusiasts. There are several obvious reasons for the burgeoning growth of the supermarkets, One, which is very obvious is that earlier assembling large parts of land in locations which offered good connectivity to the rest of the city was a difficult task. Today some of the bottlenecks are gradually easing.